Electrochemical sensor using gold nanoparticles and plasma pretreated graphene based on the complexes of calcium and Troponin C to detect Ca2+ in meat. (1st March 2020) - Fan, Xiaoquan; Xing, Lujuan; Ge, Panwei; Cong, Laixin; Hou, Qin; Ge, Qingfeng; Liu, Rui; Zhang, Wangang; Zhou, Guanghong
Highlights: It is the first time to apply electrochemical methods to measure the Ca 2+ in meat. Materials used in our study are firstly based on the specificity of cTnC for Ca 2+ . The sensor has much lower linear limit than previous research. The sensor is highly stable, sensitive and accurate in detecting Ca 2+ . Abstract: A simple electrochemical sensor was developed to determine the concentration of Ca 2+ in meat. Graphene was treated with oxygen plasma for 10 s and 30 s comparing with the pristine graphene. Through analyzing morphology and chemical composition, the graphene with the lowest defect density was chosen to mix with bovine serum albumin molecule-functionalized gold nanoparticles. It was interesting that only a few gold nanoparticles were trapped in the graphene with 10 s plasma treatment. Then, under the optimal condition measured, the limit of detection was detected as 3.9 × 10 −8  M with a linear relationship from 5 × 10 −8 to 3 × 10 −4  M. Finally, the proposed electrochemical method was applied to detect Ca 2+ in the pork sample with stability and reproducibility verified by parallel detections. Thus, the proposed method demonstrates its potential for effectively detecting Ca 2+ in meat and prominently reduces time consumption on operations and pretreatments.